(untitled) (River Edge, NJ, 2003)
The biannual ISAAC congresses provide information about recent progress in the whole area of analysis including applications and computation. This book constitutes the proceedings of the third meeting.
Keywords: Mathematical analysis,Mathematical physics; Vâtk lý toán,Phân tích toán học